2
$\begingroup$

Let A and B be sets. Show that the following equality holds: $$(A-B) \cup (B-A)=(A \cup B)-(A \cap B)$$

So, if one want to show that this equality holds via the tabluea method, one needs to translate the above into propositional logic.

Is the following translation correct? $$(A \wedge \neg B) \vee (B \wedge \neg A) \Leftrightarrow (A \vee B) \wedge (\neg A \wedge \neg B) $$

$\endgroup$
1
  • 2
    $\begingroup$ $(A∪B) − (A∩B)$ is $(A∪B) ∩ (A∩B)^C$. Thus, we have: $\lnot (A \land B)$. $\endgroup$ – Mauro ALLEGRANZA Dec 14 '17 at 8:00
2
$\begingroup$

It is not correct and should be:$$(A\wedge\neg B)\vee(B\wedge\neg A)\iff\left(A\vee B\right)\wedge\neg\left(A\wedge B\right)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.